Respuesta :
Answer:
f(-3) = 18
Step-by-step explanation:
We need just substitute x with (-3) and calculate it.
f(-3) = (-3)² -2*(-3) + 3 = 9 + 6 +3 = 18
The value of f(-3) according to the function, f(x) = x2 – 2x + 3 is; f(-3) = 18.
According to the question;
- We are required to evaluate f(-3) provided that f(x) = x2 – 2x + 3.
To evaluate the value of f(-3);
We must substitute -3 as the value of x into the expression for the function, f(x) as follows;
- f(-3) = (-3)² -2(-3) + 3
- f(-3) = 9 + 6 + 3
- f(-3) = 18.
Read more:
https://brainly.com/question/3559047